Predominant failure mechanisms at the Kiirunavaara mine footwall - Svartsjaern, Mikael (Luleå tekniska universitet, Geoteknologi, 2015)
The Luossavaara-Kiirunavaara Aktiebolag (LKAB) Kiirunavaara mine is a large scale sub-level caving (SLC) mine in northern Sweden. The use of SLC as a mining method inherently causes significant rock mass movements above the extraction level. It has been one of the objectives of LKAB since the early 1990s to accurately forecast the global stability of the footwall in relation to the inherent rock mass movements from the sub-level caving. In the Kiirunavaara case, the dip of the main ore-body entails the footwall to develop as a rockslope confined by cave material from the hangingwall. It has been discussed that the global stability of the footwall is likely related to the interaction of two or more failure mechanisms acting in combination, however, the true footwall failuremechanisms are still debated. The objective of this thesis is to study and evaluate the footwall behaviour and determine the predominant mechanisms by combining data from field observations, numerical modelling and seismic data analysis. Field data was collected through damage mapping on decommissioned levels in the footwall on depths between 120 to 700 m for the full 4 km ore-body length. From the mapping data a conceptual boundary between damaged and undamaged footwall rock was established in the form of a damage boundary surface. The 3D geometry of the damage surface was analysed and a section was extracted and used in calibrating numerical models for simulatingthe footwall behaviour in response to mining. A parametric study was performed to highlight high impact inputs and study plausible origins of the conceptual damage surface. A base case model was adopted to explain the failure evolution and used in the analysis of seismic data. The seismic data was analysed with respect to origin mechanisms as well as temporal and spatial location patterns. The outline of the large scale footwall fracturing interpreted from the conceptual damage surface was geometrically complex. No single principal failure modes could be identified from evaluating the ...